2014
DOI: 10.1002/pd.4350
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal examination and postmortem findings in fetuses with gastroschisis and omphalocele

Abstract: Objectives: We studied the rate of chromosomal cytogenetic abnormalities of fetuses with abnormal sonographic findings detected in the late second or third trimester. Methods: Retrospective analysis of all women at or beyond 23 gestational weeks at a single medical centre, who underwent amniocentesis during January 2012 to December 2015, indicated for abnormal sonographic findings that first appeared and were diagnosed at late second or third trimester. Primary endpoints were the results of fetal karyotype and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…One point that should be mentioned is that we did not see isolated micrognathia cases; all 20 cases had multiple‐system anomalies. Also, the detection rates for holoprosencephaly and cystic hygroma were lower in our study than those reported previously, and the detection rates for fetuses with gastroschisis were in the range of 0% to 4%, whereas our result was higher than that. Maybe the amount of sample sizes and selection biases were the reasons for this difference.…”
Section: Discussioncontrasting
confidence: 96%
“…One point that should be mentioned is that we did not see isolated micrognathia cases; all 20 cases had multiple‐system anomalies. Also, the detection rates for holoprosencephaly and cystic hygroma were lower in our study than those reported previously, and the detection rates for fetuses with gastroschisis were in the range of 0% to 4%, whereas our result was higher than that. Maybe the amount of sample sizes and selection biases were the reasons for this difference.…”
Section: Discussioncontrasting
confidence: 96%
“…Omphalocele is an abdominal wall defect that bowel and/or other visceral organs herniate from umbilical ring which is covered by peritoneal sac. The prevalence for 11-14 weeks is 1:1000 and the incidence for live-born is 1-2, 5:10000 [1]. Omphalocele pathogenesis is not clear but familial and genetical factors play an important role to development of omphalocele [1].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence for 11-14 weeks is 1:1000 and the incidence for live-born is 1-2, 5:10000 [1]. Omphalocele pathogenesis is not clear but familial and genetical factors play an important role to development of omphalocele [1]. In the 11-14 weeks, it can be diagnosed easily by ultrasound scan used for nuchal translucency.…”
Section: Discussionmentioning
confidence: 99%
“…Sonographic detection of an omphalocele can be made as early as 12 weeks' gestation ( Figure 4). [11][12][13][14] Earlier diagnosis is discouraged as normal physiologic herniation of the fetal small bowel can lead to false positives. Although an exception is the presence of extracorporeal liver which would indicate the presence of an omphalocele.…”
Section: When and How Can Omphalocele Be Diagnosed?mentioning
confidence: 99%
“…Missed diagnosis or late diagnosis of omphalocele in the third trimester is rare (5%-7%). 13,[15][16][17][18][19] The principal sonographic finding is the presence of a membrane covered mass adjacent to the fetal abdomen at the level of the umbilical cord insertion (Box 1). 2 Virtually, all omphaloceles contain small bowel loops and up to 80% contain parts of the liver.…”
Section: When and How Can Omphalocele Be Diagnosed?mentioning
confidence: 99%